PENGARUH SITZ BATH AIR HANGAT TERHADAP LAMA PENYEMBUHAN LUKA PERINEUM PADA IBU POST PARTUM DI PMB PONIRAH KOTA METRO - Martini; Yetti Anggraini (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: Tearing a perineal wound during labor usually occurs so that the baby's head can be born quickly. Perineal wounds can be due to spontaneous tears or because of an episiotomy. The incidence of perineal rupturein PMB Ponirah as much as 69% 65% of mothers trip advisor perineal wounds. The impact of perineal rupture can cause pain. Objective: The purpose of this study was to determine the effect of warm baths on the wounds experienced by postpartum mothers in PMB Ponirah Metro City District. Methods: This study is a pre-experimental quantitative study with the Static Group Comparison design. The large sample consisted of 30 people, consisting of 15 people as sizt bath and 15 people as not sizt bath. In this study used the Mann Whitney test. Results: The results of the study showed the average reserve of bath sitz on day 5 and there was no reserve for bathing sitz on the 7th day. The result of the effect is the effect of warm baths on the duration of perineal wound healing in postpartum mothers. Conclusion: Sitz bath can accelerate wound healing and help with perineal pain. Keywords: Perineal pain, Perineal wound healing,Sitz bath